FIELD TRIALS OF MOLLUSCICIDE (WL 8008) IN BILHARZIASIS CONTROL PROJECT AREA, IN IRAN - J. Massoud; F. Arfaa; M. Mousavi (Tehran University of Medical Sciences, 1973)
Field trials of molluscicide WL8008 (N-tritylmorpholine) were carried out in Khuzestan, Iran. The liquid 2 (FX/28), a 16.5 w/v emulsifiable concentrate in tetrachloroethylene in concentrations of 0.25 ppm and 0.5 ppm was used against Bulinus truncatus and Lymnaea gedrosiana in standing and running water systems . Bio-assay tests and laboratory experiments were made parallel to the field trials. Only a few of the B.truncatus were affected by 0.25 ppm of N-tritylmorpholine, but L.gedrosiana proved to be more susceptible to the chemical and an almost complete kill of L.gedrosiana was achieved. A concentration of 0.5 ppm completely killed both B.truncatus and L.gedrosiana, but had no effect on egg-masses. N-trityl-morpholine may play an important part in future snail control projects, particularly on Lymnaea snails.